Tackling Energy Poverty Through Behavioral Change: A Pilot Study on Social Comparison Interventions in Social Housing Districts - Caballero, Nicolas; Della Valle, Nives (Frontiers in Sustainable Cities, 2021)
Behavioral Economics has in recent years played a key role in informing the design of non-price interventions aimed at promoting energy conservation behaviors in residential areas. Some of the most influential contributions of the discipline in an applied setting have centered around the development of norm-based interventions. The success that these interventions have had in specific contexts presents an opportunity to utilize them as tools for tackling a prevalent type of poverty at the EU level: energy poverty. Recent contributions to the literature highlight the role of inefficient energy behavior as a significant driver of this particular type of poverty, which is characterised by an inability to afford the basic energy services necessary to guarantee a decent standard of living. Therefore, the effectiveness of norm-based interventions in vulnerable populations merits further investigation to determine whether this approach can suitably address the behavioral components of energy poverty by promoting efficient energy consumption and conservation efforts. This is particularly imperative when combined with retrofitting innovations, as it can help avoid negative behavioral responses often associated with the implementation of efficiency upgrades, such as rebound effects. This study reports on a pilot conducted in an exemplary social housing context (located in Bolzano, Italy) with the aim to assess the effectiveness of social comparison interventions in energy vulnerable groups. Using a design that combines appeals to injunctive and descriptive norms embedded within In-Home Devices (IHD) in recently retrofitted homes, our objective is to set a basis for the assessment of effectiveness of these types of interventions in social housing populations. Our study seeks to provide useful methodological insights to policy makers on how to effectively design behaviorally informed interventions aimed at tackling energy poverty.